Evaluation of the public health risk for autochthonous transmission of mosquito‐borne viruses in southern Switzerland. Issue 2 (4th December 2019) - Ravasi, D.; Parrondo Monton, D.; Guidi, V.; Flacio, E.
Abstract: Epidemics of mosquito‐borne diseases such as chikungunya and dengue fever are becoming more frequent around the world. In Switzerland, autochthonous cases have not been reported so far, although the presence of the vector Aedes albopictus in urban areas of southern Switzerland increases the risk of indigenous transmissions subsequent to imported cases. In 2018, the potential risk of an outbreak of arboviral diseases was assessed in five municipalities of southern Switzerland. The population abundance of Ae. albopictus was evaluated during the mosquito active season by the mean number of Ae. albopictus bites per day per person (estimated using the human landing collection method) and the risk of outbreak in the case of the introduction of chikungunya, dengue or Zika viruses was estimated. In the five localities investigated, no epidemic risk appeared to be present for any of the arboviruses taken into consideration in the initial months (i.e. mid‐May to end of July) of Ae. albopictus activity. In the case of the introduction of chikungunya (mutated or not), dengue (serotype 1) or Zika (African lineage) viruses during mid‐end August, an epidemic could have occurred in all the municipalities investigated. In mid‐end September, the introduction of same arboviruses could have led to an epidemic in three of the five municipalities investigated. Abstract : We assessed the potential risk of an outbreak of arboviral diseases CHIKV, DENV and ZIKV in municipalities of southern Switzerland where the vector Ae. albopictus is well established. No epidemic risk was detected from May to July. In August and September, an introduction of arboviruses could lead to an epidemic in the majority of the municipalities investigated. Results obtained indicate that the risk for epidemic exists mainly in presence of important breeding hotspots.